Approaches to Study Living Foraminifera Collection, Maintenance and Experimentation - Kitazato, Hiroshi; M. Bernhard, Joan (Environmental Science, 2014)
Foraminiferal cultures now serve as tools for researching biological, environmental, and geological topics. However, the biological backgrounds, in particular the natural histories of foraminifera, largely remain unclear. It is also true that the different techniques used in different subdisciplines are a setback to fully understanding the subject. Taken together, these factors prevent progress in experimental approaches to foraminiferal studies. This book aims to share and exchange knowledge between researchers from different subdisciplines, and the book should interest not only foraminiferal researchers but also scientists who are working with marine organisms to explore questions in relation to biology, geology, and oceanography.